The Steroid Hormone Profile in Etawah Crossbreed Goat While Ovulation Induced using The Selectsynch Method - Aftabuddin Rz, Muhammad; Srianto, Pudji; Nidom, Chairul Anwar; Madyawati, Sri Pantja; Sardjito, Trilas; Ismudiono, Ismudiono (Universitas Airlangga, 2022)
This study aimed to provide alternative information and solutions in an effort to increase reproductive productivity in etawah crossbreed goats (PE). The sample used in this study was 10 female PE with an average age of 2.5 - 3 years and primiparous at least . Ovulation induction was performed using 0.1 mg intra-muscular Gonadotropin-Releasing Hormone (GnRH), after seven days injection of Prostaglandin F2α (PGF2α) was given as much as 2.5 mg submucosa of the vulva, followed by a second injection of GnRH as much as 0,2 mg intramuscular in samples that have really experienced heat and selected selectively according to the signs of natural heat shown by the sample and followed by insemination as much as 2 doses or 0.50 ml of frozen semen. Blood sampling was performed at H0, H7th, H14th and H21th after insemination. All blood samples were collected and progesterone and estrogen hormone profiles were examined using the ELISA method. From the results of the ELISA test, the mean progesterone hormone profile H0 = 4.798 ng / ml, H7th = 4.887 ng / ml, H14th = 4.824 ng / ml, H21th = 5.148 ng / ml. The profile of the hormone estrogen at H0 = 19,461 pg / ml, H7th = 17,457 pg / ml, H14th = 18,248 pg / ml, H21th = 17,515 pg / ml. This study showed an increase in the levels of the progesterone hormone at H0 to H7th, then slightly decreased in H14th and a significant increase in H21th. For the estrogen hormone, there is a decrease from H0 to H7th then there is a slight increase in H14th and decreases again in H21th.